HIV Awareness and Risk Behavior among Pregnant Women in Mateete, Uganda (2010). (15th September 2011) - Sandqvist, Josefin; Wahlberg, Johanna; Muhumuza, Elly; Andersson, Rune
Abstract : Background . The aim of the study was to evaluate current knowledge, risk behavior, and attitudes among pregnant women in Mateete, Uganda. Methods . We collected 100 questionnaires and performed 20 interviews among women who attended antenatal care. Findings . All the women had heard about HIV/AIDS, and 92% were aware of mother-to-child transmission. The women overestimated the risk of achieving the virus since 45% believed in transmission by mosquitoes and 44% by kissing. Many pointed out that married women as a group were infected more often because of unfaithful partners who refused to use condoms during sex. Conclusion . The women were well aware of the routes of HIV transmission. Schools and governmental campaigns have played an important role in educating people about the disease but there is still a great need to reach out to people in rural areas with both health care and correct information.